The Impact of Employer Brand on Retaining the Knowledge Employees in the Telecommunication Sector in Sri Lanka - J. N. Jenitta (Research Parks Publishers, 2021)
The research aims to find out the impact of employer brand on retaining the knowledge employees in the telecommunication sector in Sri Lanka. By using the primary data, the researcher tends to find the factors which make the knowledge employees more attractive and to identify the impact of employer brand on retaining the knowledge employees with identifying the mediating effect of Job satisfaction. Based on this findings telecommunication sector’s brand has significant impact on knowledge employee retention. Also it was found that there is a mediating effect of job satisfaction in between employer brand and employee retention. Multiple regression revealed that dimensions of employer brand such as economic value, social value, interest value and reputation value significantly affect the knowledge employee retention but the dimensions of development value, application value and personal value are not significant. Furthermore, a simple regression analysis showed that there is a significant impact employer brand on job satisfaction and knowledge employee retention.